Assessment of health sciences academic advisors’ mental health literacy and their experiences with students facing mental health problems - Fatimah Raji; Nahed Morsi; Alaa Mahsoon; Loujain S. Sharif (Belitung Raya Foundation, Indonesia, 2022)
Background: Owing to everyday educational activities, academic advisors often have to deal with mental health problems among students. Therefore, their mental health literacy must be assessed to determine whether they can detect mental health problems when working with the students. Objective: This study aimed to assess health sciences academic advisors’ mental health literacy and their experiences dealing with university students facing mental health challenges. Methods: A cross-sectional descriptive study was undertaken among a convenience sample of 133 health sciences academic advisors at the medical campus of a public university in Jeddah, Saudi Arabia. An electronic self-administered questionnaire using the Mental Health Literacy Scale (MHLS) was used to appraise participants’ recognition, knowledge, and attitudes toward ways to solve mental health difficulties. Data collection was completed from November 2020 to February 2021. Descriptive statistics, Student’s t-test for independent samples, One-Way Analysis of Variance (ANOVA), and Tukey’s test were selected for data analysis. Results: Academic advisors were found to be highly literate about matters of mental health. The mean mental health literacy score was statistically significantly higher in those advisors who were lecturers, assistant professors, associate professors, and professors (p <0.001). Additionally, the mean scores were significantly higher among advisors with a teaching role of lecturer rather than those who did not have the teaching role of a clinical supervisor (t = -2.331; p = 0.021). Conclusions: The academic advisors had an elevated level of mental health literacy, and the highly experienced academic advisors could deal better with students having mental health problems. Hence, it is essential to continue to provide educational programs and training on mental health literacy to academic advisors, as it helps them identify the signs of mental health complications. Furthermore, it improves their skills and confidence when they offer student support in coping with mental health issues.